Implementasi Digital Forensik Aplikasi Dompet Digital Dan Pesan Instan Pada Android Dengan Menggunakan Metode NIST - Delia Paramita Harahap (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2022)
It cannot be denied that technology plays a very important role in today's society. The important role of technology not only brings positive influences but also negative influences. The resulting positive influence is the convenience that we can feel in carrying out our daily activities, one of which is by making digital payments anytime and anywhere, while the negative effect is that there are crimes that can attack, be it cyberbullying or cybercrime. Implementation of digital forensics using the NIST (National Institute of Standards and Technology) method with the stages of collection, examination, analysis, and reporting to help find digital evidence. By using the Oxygen Forensic Detective and MOBILedit Forensic tools, success in finding evidence of exchanged messages, images, user information, payment transactions, product information, and images in deleted data files. The success rate of the two forensic tools used is quite different, Oxygen Forensic Detective has a success rate of 91.7% while MOBILedit Forensic has a lower success rate of 66.7% in finding digital evidence.